(untitled) (Research, Society and Development, 2021)
The mandible is the only mobile bone in the face and has a role in mastication, swallowing, speech and facial esthetics. It is frequently fractured, having a varied origin, with a prevalence of up to 40 years of age, in cases of fall from standing height, it is more frequent in children and the elderly. A 64-year-old male patient, victim of a motorcycle accident, attended the Maxillofacial Surgery and Traumatology service at the Teresina Emergency Hospital. On clinical examination, he presented edema, lacerations and excoriations on the face on the right side, he presented a bone step on palpation of the mandible in the region of the right angle and symphysis. The image exam showed, in the computed tomography, the presence of a discontinuity of the mandibular arch with multiple fracture lines, in the region of the right angle, right body and symphysis of the left mandible. Closing the diagnosis in Complex fracture of the mandible, thus forwarding the surgical intervention for reduction and fixation of the fracture. Four 2.0 system boards were used. Local infiltration with xylocaine with 2% vasoconstrictor was performed, incision for Risdon access (submandibular), fracture exposure, reanatomization of bone fragments and osteosynthesis with two 2.0 plates and 15 screws in the compression and tension area, the same was performed in the intraoral access in the symphysis region. Finally, suture by planes. The patient was discharged from the hospital within one day and continued with outpatient follow-up. Based on the case presented, in cases of mandible fractures, the extraoral risdon and intraoral access are effective and safe.